The energy balance of a CHP unit fuelled by mine gas - Kalwar, Adam; Filipek, Roman; Madejski, Paweł; Pytel, Krzysztof; Kurdziel, Franciszek (Wydawnictwa AGH, 2024)
This paper presents the results of a study of a gas engine heat recovery system in terms of efficient use of the energy contained in the fuel, with the study performed determining the most efficient variant of gas engine operation. A comparison between the manufacturer’s data and the performance results was also made. Simulations performed on the system model allowed the optimum engine load range to be determined. The results of the analyses also indicated which variant of the engine heat recovery system is the most effective.

W artykule przedstawiono wyniki badań układu odzysku ciepła silnika gazowego pod kątem efektywnego wykorzystania energii zawartej w paliwie, co pozwoliło na określenie najbardziej wydajnego wariantu pracy silnika gazowego. Dokonano również porównania danych producenta z wynikami osiąganych parametrów eksploatacyjnych. Przeprowadzone symulacje na modelu układu pozwoliły wyznaczyć optymalny zakres obciążeń silników. Wyniki analiz wskazały również, który wariant układu odzysku ciepła z silnika jest najbardziej efektywny.
Bilans energetyczny agregatu kogeneracyjnego zasilanego gazem kopalnianym
Mining - Informatics, Automation and Electrical Engineering
Keywords: gas engines; mine gas; coke-oven gas; gas fuel; cogeneration; gas engines; mine gas; coke-oven gas; gas fuel; cogeneration